Influence of Seasons on Seminal Attributes of Crossbred Bulls and its Implications on Fresh, Diluted and Cryopreserved Semen - Kapale, PM; Nagvekar, AS; Dhande, PL; Ingole, SD; Ramteke, BS; Gadegaonkar, GM (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was conducted on eight crossbred bulls (HFxGir, 50-75% HF inheritance) under Konkan Development Corporation Ltd. of Maharashtra. Semen ejaculates obtained at monthly interval were used for this study. Semen samples were subjected to routine macroscopic and microscopic evaluation. The study was planned for three seasons, viz., summer, winter and monsoon. The ejaculates were divided into two parts: one part was used for analysis as fresh semen and second part was diluted using egg yolk extender and then cryopreserved. It was observed that the sperm motility and live sperm percentage were significantly low during summer season as compared to winter and monsoon season in fresh semen samples. The semen volume was significantly higher during summer season whereas the sperm concentration was higher in winter season. The colour, consistency and density were not affected by season. Thus, it was concluded that summer season adversely affects the seminal attributes which may result in low quality semen production. herd reproductive effectiveness (Berry et al., High quality bull semen is required for successful fertilization and improved herd health. The semen from individual bull may be used for many females and poor quality semen may affect herd fertility and productivity of the farm by lengthening calving intervals. In the breeding systems, their bio-economical effectiveness depends on bull fertility and performance in the field.